PEMBERDAYAAN INDUSTRI KECIL KERIPIK PISANG DALAM UPAYA MENUJU INDUSTRI MANDIRI - Pudjihastuti, Isti; Supriyo, Edy; Hartati, Retno (METANA, 2011)
Abstract                                                                          The development of micro industries, in banana chip micro industry to the member of group which is culinary enterprise Pemalang speciallized is give suitable solution to consument for giving natural culinary with high nutrition value independently and cheap.The development of micro industries is circular activity that consist of briefing about the use of gelatse system in banana chip production by naturally and independently, the suitable tachnique of banana chip production, production of furnace completely by steack as pilot plan, assitancy when the producer makes snack in gelatse system. Moreover, the taste of snack more delicious, the market bigger.